Endoscopic Neck Surgery for Thyroid Carcinoma. Issue 3 (2001) - Kitano, Hiroya; Kinoshita, Takashi; Kataoka, Hideyuki; Hirano, Masamitsu; Takeuchi, Eiji; Kitajima, Kazutomo; Fujimura, Masaki
Abstract : In the past 5 years, endoscopic neck surgery has been performed by various surgeons in Japan. However, many problems remain to be solved, including indications for this related in malignant thyroid tumors. For small thyroid cancers and legions suspected of malignancy, we found that we could obtain radicality in endoscopic neck surgery that was comparable to that attainable by conventional methods. Here, we describe our recent endoscopic surgical experience in five patients with preoperative diagnoses of definite or suspected thyroid carcinoma.